2013
DOI: 10.1002/stem.1357
|View full text |Cite
|
Sign up to set email alerts
|

Autologous adipose tissue-derived stem cells treatment demonstrated favorable and sustainable therapeutic effect for Crohn's fistula

Abstract: Fistula is a representative devastating complication in Crohn's patients due to refractory to conventional therapy and high recurrence. In our phase I clinical trial, adipose tissue-derived stem cells (ASCs) demonstrated their safety and therapeutic potential for healing fistulae associated with Crohn's disease. This study was carried out to evaluate the efficacy and safety of ASCs in patients with Crohn's fistulae. In this phase II study, forty-three patients were treated with ASCs. The amount of ASCs was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
208
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(216 citation statements)
references
References 44 publications
5
208
0
3
Order By: Relevance
“…During the past year, STEM CELLS has been proud to publish exciting clinical advances in treating steroid-refractory Graft versus Host disease [1], Cerebral Palsy [2], Crohn's fistula [3], and treating alveolar bone defects with an injectable tissue engineered stem cell product, avoiding the donor site morbidity associated with bone autograft [4].…”
mentioning
confidence: 99%
“…During the past year, STEM CELLS has been proud to publish exciting clinical advances in treating steroid-refractory Graft versus Host disease [1], Cerebral Palsy [2], Crohn's fistula [3], and treating alveolar bone defects with an injectable tissue engineered stem cell product, avoiding the donor site morbidity associated with bone autograft [4].…”
mentioning
confidence: 99%
“…A summary of study characteristics is shown in Table  1, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported the outcome of stem cell therapy; five open label/phase I or II trials59 60, 63 65, 66, with longer‐term follow‐up61 of the cohort initially reported by Cho et al 60. in 2013.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations